A polymethoxyflavone mixture extracted from orange peels, mainly containing nobiletin, 3, 3', 4', 5, 6, 7, 8-heptamethoxyflavone and tangeretin, suppresses melanogenesis through the acidification of cell organelles, including melanosomes. Issue 1 (October 2017) - Yoshizaki, Norihiro; Hashizume, Ron; Masaki, Hitoshi
Highlights: Polymethoxyflavone suppresses melanogenesis in human melanoma cells. Polymethoxyflavone promotes tyrosinase degradation by lysosomes. Polymethoxyflavone acidifies cell organelles, including melanosomes. Neutralization of cell organelles prevents polymethoxyflavone from suppressing melanogenesis. Polymethoxyflavone inhibits the localization of tyrosinase into melanosomes by acidifying cell organelle(s). Abstract: Background: Skin color is determined by melanin contents and its distribution. Melanin is synthesized in melanosomes of melanocytes, catalyzed by tyrosinase, melanogenic enzymes. Regarding the process of melanin synthesis, melanosomal pH is considered to play an important role, because it has been reported to differ between Caucasian and Black melanocytes. Objective: Although polymethoxyflavone (PMF) has many beneficial effects, it has not been reported which PMF suppresses melanogenesis. In this study, we identified the mechanism underlying the effect of PMF on melanogenesis Methods: We determined the effects of a PMF mixture extracted from orange peels on melanogenesis, on tyrosinase expression, on the localization of tyrosinase and on the acidification of organelles, including melanosomes, in HM3KO human melanoma cells. Results treatment: with the PMF mixture elicited the suppression of melanogenesis, the degradation of tyrosinase in lysosomes and the mislocalization of tyrosinase associated with the acidification of intracellular organelles, including melanosomes. The neutralization of cell organelle pH by ammonium chloride restored melanogenesis and the correct localization of tyrosinase to melanosomes, which had been suppressed by the PMF mixture. Conclusion: These results suggest that the PMF mixture suppresses the localization of tyrosinase to melanosomes and consequently inhibits melanogenesis due to the acidification of cell organelles, including melanosomes.